Venous thromboembolism in SARS-CoV-2 patients: only a problem in ventilated ICU patients, or is there more to it?. Issue 1 (30th July 2020) - Criel, Maarten; Falter, Maarten; Jaeken, Jasmien; Van Kerrebroeck, Margaretha; Lefere, Isabelle; Meylaerts, Liesbeth; Mesotten, Dieter; vander Laenen, Margot; Fivez, Tom; Thomeer, Michiel; Ruttens, David
Venous thromboembolism (VTE) is a well-known complication in hospitalised patients [1–5]. Risk factors include older age, obesity, immobilisation, active malignancy, systemic inflammatory response syndrome (SIRS), (major) surgery, thrombophilia and a history of thromboembolism [2, 5]. In 1884, Rudolph Virchow first described the underlying pathophysiological mechanisms, which consist of endothelial cell dysfunction/inflammation, low blood flow and blood hypercoagulability. Current guidelines recommend the use of thromboprophylaxis in acutely ill medical patients who are at high risk for VTE (Padua score ≥4, IMPROVE (International Medical Prevention Registry on Venous Thromboembolism) score ≥2) [6]. However, in medical practice, less than half of the patients at risk receive adequate thromboprophylaxis [4]. Insidious venous thromboembolism (VTE) is mainly a problem in ICU-ventilated SARS-CoV-2 patients, while patients in the general ward, treated with thromboprophylaxis (0.5 mg·kg −1 ), had a low incidence of insidious VTE https://bit.ly/2Yl8jft